1981
DOI: 10.1073/pnas.78.6.3624
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of calcium in exocytosis: mechanism of nematocyst discharge as shown by x-ray microanalysis.

Abstract: Mature nematocysts of the sea anemones Rhodactis rhodostoma and Anthopleura elegantissima contain a fluid that has a high concentration of solutes and is extraordinarily rich in calcium (ca. 500-0 mmol/kg wet weight); this contrasts with the surrounding cytoplasm which is rich in potassium but poor in calcium. The undischarged capsule is surrounded by a membrane that probably acts as a selective permeability barrier between the cytoplasm and the nematocyst fluid. During discharge the nematocyst moves to the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(34 citation statements)
references
References 12 publications
5
28
1
Order By: Relevance
“…Furthermore, calcium concentration in the mesogloea of the oral epithelium approaches 18·mmol·kg -1 . These values are similar to those observed in settled larvae of Pocillopora damicornis been recorded at less than 5·mmol·kg -1 wet mass (reviewed by Gupta, 1993), although a concentration of 9·mmol·kg -1 wet mass has been reported for the cytoplasm of nematoblast cells in an anemone (Lubbock et al, 1981). Our values are considerably higher than the estimate of 2.8·mmol·l -1 derived from 45 Ca compartment analysis in Stylophora pistillata .…”
Section: High-resolution Ion Microprobe (Nanosims) Analysiscontrasting
confidence: 50%
“…Furthermore, calcium concentration in the mesogloea of the oral epithelium approaches 18·mmol·kg -1 . These values are similar to those observed in settled larvae of Pocillopora damicornis been recorded at less than 5·mmol·kg -1 wet mass (reviewed by Gupta, 1993), although a concentration of 9·mmol·kg -1 wet mass has been reported for the cytoplasm of nematoblast cells in an anemone (Lubbock et al, 1981). Our values are considerably higher than the estimate of 2.8·mmol·l -1 derived from 45 Ca compartment analysis in Stylophora pistillata .…”
Section: High-resolution Ion Microprobe (Nanosims) Analysiscontrasting
confidence: 50%
“…The latter theory received considerable support from the investigation of Lubbock et al (1981). This work was carried out by X-ray microanalysis of 1-2 m cryosections of tentacles and acrorhagi in both the hydrated and freeze-dried states.…”
Section: Cnidaementioning
confidence: 98%
“…One consequence of the fact that multiple cell types are involved in the regulation of discharge has been the challenge of localizing the site of action of some experimental manipulations. For example, several studies have concluded that voltage-gated Ca 2+ channels are involved in discharge (Lubbock et al, 1981;Gitter and Thurm, 1993;Gitter et al, 1994), and while it has been assumed that Ca 2+ channels play a direct role on the exocytotic event underlying discharge, the possibility that those channels are present at synapses within the nerve nets that innervate cnidocytes cannot be excluded. Distinguishing between these possibilities is compounded by the small size and diffuse nature of many of the cells in question, particularly the neurons.…”
Section: 1mentioning
confidence: 99%
“…Because of the complexity of the cell, and the fact that a cnidocyte can be used only once, their discharge is very tightly regulated to minimize what is likely to be the considerable energetic cost of replacement. Studies of the regulation of cnidocyte discharge have employed a variety of physiological (Gitter et al, 1994;Brinkmann et al, 1995;Purcell and Anderson, 1995;Salleo et al, 1996), structural (Lubbock et al, 1981;Westfall and Grimmelikhuijzen, 1993;Westfall, 2004) and histochemical approaches (Anderson et al, 2004;Kass-Simon and Scappaticci, Jr, 2004), using representatives of all cnidarian classes. Given that cnidocyte discharge is thought to be an exocytotic event, special attention (Lubbock et al, 1981;Gitter and Thurm, 1993;Gitter et al, 1994) has been given to the potential role of voltage-gated ionic currents, particularly Ca 2+ currents of the type that trigger exocytosis at synapses and exocrine cells (Sudhof, 2004).…”
Section: Introductionmentioning
confidence: 99%